Natural Zeolite as Mo and MoP Catalysts Support for Catalytic Deoxygenation of Jatropha Oil - Aziz, Isalmi; Farhan, Muhammad; Saridewi, Nanda; Azizah, Yulyani Nur; Muawanah, Anna; Nurbayti, Siti; Dwiatmoko, Adid Adep; Adhani, Lisa (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Non-edible oil, such as Jatropha oil, is an interesting feedstock for the development of renewable diesel (green diesel). Catalytic deoxygenation using natural zeolite-supported Mo-based catalysts is a promising process for the conversion of Jatropha oil to green diesel. Mo and MoP catalysts supported on natural zeolite were synthesized by wet impregnation at a concentration of 5% (w/w). The catalysts were characterized by XRD, XRF, SAA and NH3-TPD. The catalysts were successfully synthesized with the appearance of Mo and MoP peaks on the catalyst diffractogram. XRF results also showed that Mo and P were present in the catalyst. Metal impregnation decreased the surface area and pore volume of the catalyst, but increased the average pore diameter. The NH3-TPD profile of the catalyst showed that the weak acid sites of both catalysts were larger than the strong acid sites. Based on the activity test of catalytic deoxygenation of Jatropha oil, the MoP/HZ catalyst produced a higher conversion (67%) and liquid product yield (79%) than Mo/HZ. This is associated with a larger pore diameter, so that the distribution of reactants on the catalyst surface is more optimal. However, the highest green diesel selectivity of 82% is produced by the Mo/HZ catalyst. The Mo/HZ catalyst is more oriented towards the HDO reaction, whereas the MoP/HZ catalyst is more oriented towards the DCO/DCO2 reaction.